Suppression May Improve Adaptation to Worry When Facing Uncertainty: Studying COVID-19 Pandemic - Khatibi, Ali; Sharpe, Louise; Dehghani, Mohsen; Ghalibaf, Erfan; Hosseinchi, Parham; Mazidi, Mahdi; Ranjbar, Seyran; Deldar, Zoha; Gevers-Montoro, Carlos; Alizadeh, Pouyan; Alidoust, Shaghayegh; Babaei, Arghavan; et al. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has been associated with increased uncertainty, fear and worry in everyone’s life. The effect of changes in daily life has been studied widely, but we do not know how emotion-regulation strategies influence adaptation to a new situation to help them overcome worry in the face of uncertainty. Here, 1064 self-selected Farsi speaking participants completed an online battery of questionnaires that measured fear of virus and illness, worry, intolerance of uncertainty, and emotion regulation (two subscales: reappraisal, suppression). We also documented the number of daily COVID-19 cases and deaths due to COVID-19 on the day in which participants completed the questionnaire. Our findings suggest a correlation between contamination fear and the number of daily-confirmed cases (r=0.11), and the number of reported deaths due to COVID-19 (r=0.09). Worry mediated the relationship between intolerance of uncertainty and fear of virus and illness (b=0.16, 0.1141